Pengaruh Country of Origin dan Brand Image Terhadap Keputusan Pembelian Produk Skincare Merek Somethinc Pada E-Commerce Tiktok Shop Studi Pada Mahasiswa Universitas Mataram - Selsilia Apriliyanti, Eby; HS, Rusminah (Postgraduate, University of Mataram, 2025)
This research aims to determine and explain the effect of Country of Origin and Brand Image on purchasing decisions on Somethinc brand skincare products in the Tiktok shop e-commerce study on Mataram University students. This type of research is quantitative associative with the data collection method used, namely a survey using a questionnaire via google form as a research instrument with a total sample of 100 respondents. The results of the analysis of this study indicate that the variables of country of origin and brand image have a positive and significant effect on the decision to purchase somethinc skincare in the e-commerce tiktok shop. The results of the instrument test state that the data in this study are valid and reliable and the classical assumption test states that the data is normally distributed.